2020
DOI: 10.1007/s10900-020-00845-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Outbreak on Healthcare Workers in Italy: Results from a National E-Survey

Abstract: Italy has been the first-hit European country to face the outbreak of coronavirus disease 2019 (COVID-19). Aim of this survey was to assess in depth the impact of the outbreak on healthcare workers (HCW). A 40-item online survey was disseminated via social media inviting Italian HCW, with questions exploring demographics, health status and work environment of respondents. A total of 527 were invited to take part in March 2020, of whom 74% (n = 388) responded to the survey. Of these, 235 (61%) were women. HCW w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
158
3
19

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(189 citation statements)
references
References 6 publications
9
158
3
19
Order By: Relevance
“…About personal protective equipment, especially at the beginning of the pandemic, personal protective equipment was not always available in Pediatric Units; in fact, it was more readily available in high-risk specialty sectors. 41 Lastly, workplace reorganization was particularly di cult in Pediatric Department. The rapid evolution of the pandemic and the progressive updating of national and local indications led to a continuous reorganization of activities, procedures, but also to a workplace remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About personal protective equipment, especially at the beginning of the pandemic, personal protective equipment was not always available in Pediatric Units; in fact, it was more readily available in high-risk specialty sectors. 41 Lastly, workplace reorganization was particularly di cult in Pediatric Department. The rapid evolution of the pandemic and the progressive updating of national and local indications led to a continuous reorganization of activities, procedures, but also to a workplace remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Operating Units, working in clinical areas requiring tasks beyond their own skills, was reported. 41,42 All these sudden changes caused an emotional overload with a signi cant increase in stress levels among pediatric HWs with negative effects on their well-being. 42 We found that self-e cacy was negatively associated to stress (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, few studies have looked at the association of factors such as PPE availability and testing, with subsequent COVID-19 infection in HCWs. [11][12][13][14][15] Finally, the association of these variables with psychological distress and clinician burn-out has not been described. While previous studies have broadly described occupational stressors and lack of availability of PPE for frontline providers, few studies have attempted to sample a broad range of both clinicians and non-clinical healthcare staff.…”
Section: Open Accessmentioning
confidence: 99%
“…In the new studies, the proportion of HCWs with coronavirus disease 2019 (COVID-19) ranged from 1.1% to 23.3% (7 studies) (2, 3, 8, 14, 35-37); SARS-CoV-2 infection (not necessarily meeting COVID-19 criteria) ranged from 0.4% to 49.6% (19 studies) (5-7, 11, 15, 17-19, 21-23, 25-29, 31-33), and SARS-CoV-2 antibodies ranged from 1.6% to 24.4% (3 studies) (13,28,30). As in the original rapid review, SARS-CoV-2 infection seemed to be somewhat less severe in HCWs than in non-HCWs (5,6,15,16), with a case-fatality rate of 0% and 1.2% in 2 studies (15,16). One analysis of all cases in Italy estimated slightly higher mortality due to COVID-19 in physicians and dentists (0.046%) than in the general population (0.039%), due to increased infection incidence (20).…”
mentioning
confidence: 77%